The predictive research of ancient wooden building internal defects compressive bearing capacity based on nondestructive testing methods. Issue 3 (1st February 2021) - Chang, Li-Hong; Chang, Xiao-Hong; Chang, Hao; Qian, Wei; Cheng, Li-Ting
Abstract: 131 small specimens and 10 scaled wood column specimen (including 2 complete specimen and 8 with different defect locations and sizes and the type is core cavity) are made with the reference to Building Formulas to research the ancient wooden building internal defects compressive bearing capacity prediction. Some researches on the relationship between the small specimens wave resistance modulus and mechanics, nondestructive testing and internal defects wood column compressive bearing capacity prediction as well as dangerous section judgment and so on. The test result suggests that there is a significant positive correlation between the wave resistance modulus and the compressive strength ( r 2 = 0.635), which is more accurate than single parameter; internal defect specimens with various locations have an impact on overall compressive bearing capacity and with the defect sectional area expanding, the compressive bearing capacity decreases continuously, the cross-sectional area of the defect is proportional to the attenuation of the relative resistance value; nondestructive method can better predict wood column ultimate compressive bearing capacity and the error is predicted less than 10%. Nondestructive testing method can better determine the most dangerous section of the test piece compared with destruction morphology results. The wooden components quality can be safely evaluated on the premise that the originality of the ancient buildings is preserved and valid data references can also be provided for renovation and reinforcement of ancient buildings wooden components.